Highly substituted benzannulated cyclooctanol derivatives by samarium diiodide-induced cyclizations - Saadi, Jakub; Brüdgam, Irene; Reissig, Hans-Ulrich (Beilstein Journal of Organic Chemistry, 2010)
A series of γ-oxo esters suitably substituted with various styrene subunits was subjected to samarium diiodide-induced 8-endo-trig cyclizations. Efficacy, regioselectivity and stereoselectivity of these reactions via samarium ketyls strongly depend on the substitution pattern of the attacked alkene moiety. The stereoselectivity of the protonation of the intermediate samariumorganyl is also influenced by the structural features of the substrates. This systematic study reveals that steric and electronic factors exhibited by the alkene and ketone subunits are of high importance for the outcome of these cyclization reactions leading to highly substituted benzannulated cyclooctanol derivatives. In exceptional cases, 7-exo-trig cyclizations to cycloheptanol derivatives have been observed. In examples with high steric hindrance the ketyl–aryl coupling can be a competing process.
Keywords: cyclooctanes; ketones; ketyls; medium-sized rings; samarium diiodide; single electron transfer; styrene derivatives; radicals